Setting the farm animal welfare scene in North America - JOHNSON, ANNA K. (Revista Brasileira de Engenharia de Biossistemas, 2008)
The main areas of interest that this paper will address are to, set the scene on what animal welfare is, the schools that one can subscribe and how this could influence the direction that farm animal welfare could go. Second, to provide an overview on some of the critical farm animal welfare events that have occurred over the past 10 years in North America and finally to detail the legislative events; past and future that will affect farm animal welfare. Animal welfare is not a term that arose in science to express a scientific concept; rather it arose in western civilization through society to express ethical concern regarding the treatment of animals. There are three "schools of welfare", the first school is feeling-based, the second is functioning-based and the third is nature-based. Over the past decade there has been an escalation of welfare related events in North America, ranging from agribusiness and marketing through to humane and animal rights groups. These events include under cover investigations that have been conducted on farm and in plants. There have been numerous campaigns against fast food chain restaurants and more recently humane and rights groups have purchased shares into these companies to voice their opinions and to have a vote. In addition there has been a push for assuring on farm animal welfare through a plethora of assessment, certification and third party auditing programs. More recently, successful legislative initiatives have altered the way producers are able to house farm animals in several states and in 2005 there was an update to the 28 hour rule. In conclusion, all individuals involved in keeping animals for food have a huge responsibility in making sure that their animals are housed, raised, transported and processed humanely. In addition agribusinesses will need to show increasing accountability back to their customers and consumers that farm animal welfare is of critical importance.